A piperidinium salt stabilizes efficient metal-halide perovskite solar cells - James Durrant (Science, 2020)
Longevity has been a long-standing concern for hybrid perovskite photovoltaics. We demonstrate high-resilience positive-intrinsic-negative perovskite solar cells by incorporating a piperidinium-based ionic compound into the formamidinium-cesium lead-trihalide perovskite absorber. With the bandgap tuned to be well suited for perovskite-on-silicon tandem cells, this piperidinium additive enhances the open-circuit voltage and cell efficiency. This additive also retards compositional segregation into impurity phases and pinhole formation in the perovskite absorber layer during aggressive aging. Under full-spectrum simulated sunlight in ambient atmosphere, our unencapsulated and encapsulated cells retain 80 and 95% of their peak and post-burn-in efficiencies for 1010 and 1200 hours at 60° and 85°C, respectively. Our analysis reveals detailed degradation routes that contribute to the failure of aged cells.